Implanting Vocabulary for Long Terms Memory through Memrise and Quizlet Applications - Fadhilawati, Dian; Ulum, Bahrul; Rachmawati, Dwita Laksmita (Jurnal Pendidikan Indonesia, 2022)
The student's ability to understand and use academic and research vocabulary was lacking. Therefore, this research tries to enhance the students' vocabulary achievement by applying Memrise and Quizlet Applications. This research applies Classroom Action Research using four procedures: Planning, Action, Observation, and Reflection. Researchers obtained data from tests and questionnaires. The results showed that vocabulary planting through the Memrise and Quizlet applications increased student achievement. In addition, students also showed a positive attitude towards the application of Memrise and Quizlet for vocabulary learning. Lecturers or teachers can use the Memrise and Quizlet Applications as a medium to motivate students and provide fun and independent learning. Vocabulary achievement improved after learning vocabulary using Memrise and Quizlet applications from the results presented above. This study also used the Memrise and Quizlet applications to instil vocabulary. Therefore, the researcher suggests that teachers or lecturers who teach use the Memrise and Quizlet applications as alternative media to instil word material in students in the long term.